Diffusion layer model for condensation of vapor with the presence of noncondensable gas under natural convective condensation. (January 2020) - Lu, Junhui; Cao, Haishan; Li, Junming
Abstract: A diffusion layer model was developed for condensation heat transfer of a vapor with noncondensable gases. The model predicts the heat transfer coefficient for free convection condensation over a vertical surface in the presence of air with consideration of the effect of the variation of the mixture molecular weight and density across the diffusion layer on the vapor diffusion. The model also takes into account the effect of the suction due to the condensation on the sensible heat transfer and fog formation. The model predictions compare well with previous experimental data and correlations. This model more accurately predicts the convection and condensation heat transfer of steam and air along a vertical surface with an average error of 14.74% and with almost all the points within ±20% error bands. The results show that the suction and fog formation significantly affect the heat transfer. For high noncondensable mass fractions, the fog formation should be considered, especially at high pressures.